Performance of Grouted Splice Sleeve Connector Under Tensile Load - Aizat, Alias; Fadilah, Sapawi; Kusbiantoro, Andri; Mohammad Amirulkhairi, Zubir; Ahmad Baharuddin, Abdul Rahman (2013)
Grouted splice sleeve connector system takes the advantages of bond-slip resistance of grout and mechanical gripping of reinforcement bars to provide resistance to the tensile force. In this system,grout acts as a load transferring medium and bonding material between bars and sleeve. This study adopted the end-to-end rebars connection method to investigate the effect of development length and sleeve diameter to the bonding performance of sleeve connector. The end-to-end method is referring to the condition where reinforcement bars were inserted into the sleeve from both ends and meet at the center before grout is filled. Eight specimens of grouted splice sleeve connector were tested under tensile load to determine their performance. Sleeve connector was designed using 5 mm thick circular hollow section (CHS) steel pipe and consisted of one external and two internal sleeves. The tensile test results show that connector with smaller external and internal sleeve diameter appear to provide better bonding performance. Three types of failure were observed in this research, which are bar fracture (outside the sleeve), bar pullout, and internal sleeve pullout. With reference to these failure types, development length of 200 mm is the optimum value due to its bar fracture type, which indicates the tensile capacity of the connector is higher than the reinforcement bar.